MANAGEMENT ASPECTS OF KUTUHA BAR WETLAND IN ASSAM - BARMAN, R.C.; KAR, DEVASHISH; DANA, S.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
A study was conducted on the management aspects of Kutuha Bar Wetland (16 ha) in the Dibrugarh district of Assam. The wetland is situated around 15 km West of Dibrugarh town.( 27'2424.93'N and 94'5253.72 E elevation 350 ft MSL). The study indicated that communitybased physical assets, Beel users participation in developmental programmes , Beel users decision making ability . Women empowerment, community-based organization, management ability of Beel Development Committee (BDC), involvement of NGOs in Beel development programmes, were found to be significantly associated with the knowledge level of Beel users on community-based fisheries management either at 1% (p<0.01) or 5% (P< 0.05%) level of probability.